VD_FINDINFO ML / 2014 / 140 vom 10. Juni 2014 - VD Tribunal cantonal (2014)
DÉPENS, DISPROPORTION, TARIFEN GÉNÉRAL | 95 al. 1 CPC (CH), 95 al. 3 let. a CPC (CH), 95 al. 3 let. b CPC (CH), 20 al. 2 TDC, 3 TDC, 6 TDC